Earthquake-based multi-hazard resilience assessment: a case study of Istanbul, Turkey (neighborhood level) - Saman Ghaffarian; Mahyat Shafapourtehrany; Umut Lagap; Maryna Batur; Haluk Özener; Rıza Evren Kılcı; Himmet Karaman (npj Natural Hazards)
Abstract We developed a model integrating 28 criteria spanning social, economic, community, environmental, and physical dimensions to evaluate earthquake resilience of Istanbul, a city with a population of 16 million and significant seismic risk, at both district and subdistrict/neighborhood levels. The resilience assessment uses the Bayesian Best-Worst Method, a multi-criteria decision-making framework that combines expert knowledge and statistical assessments. The results reveal that Istanbul’s overall Resilience Score (RS) is 0.48, on a 0-1 scale, suggesting a moderate capacity to endure and recover from seismic events. Catalca, Adalar, and Arnavutkoy rank among the most resilient districts, whereas Esenler and Gungoren exhibit lower resilience. On a subdistrict level, Suleymaniye (Fatih) has the highest RS at 0.59, while Yavuz Sultan Selim (Fatih) ranks the lowest with 0.22. These findings provide actionable and practical data-driven insights for policymakers and urban planners, underscoring the need for targeted interventions to improve resilience in high-risk areas in Istanbul.